Synthesis of glucuronic acid derivatives via the efficient and selective removal of a C6 methyl group. Issue 5 (1st February 2017) - Hou, Zhuang; Liu, Yang; Zhang, Xin-xin; Chang, Xiao-wei; Cheng, Mao-sheng; Guo, Chun
Graphical abstract: A method for exceptionally selective removing the C6 methyl protecting group by potassium hydroxide without affecting the benzoyl protecting groups on the C2, C3 and C4 hydroxyl groups of certain glucuronic acid derivatives in high yields (95–99%) was reported. Highlights: Highly effective and efficient method for synthesis of glucuronic acid derivatives. Exceptionally selective removing the C6 methyl from glucuronic acid ester. Mild conditions; short reaction time; lower cost; easy operation; excellent yields. Rapid access to relevant carbohydrates in a labor-saving and economical manner. Abstract: This investigation is related to the development of a general strategy for the synthesis of certain glucuronic acid derivatives. In particular, we report exceptionally selective conditions for removing the C6 methyl protecting group by potassium hydroxide without affecting the benzoyl protecting groups on the C2, C3 and C4 hydroxyl groups in high yields (95–99%). The present method proves to be efficient and environmentally friendly in terms of short reaction time, high yield and the single product.